How can students contribute? A qualitative study of active student involvement in development of technological learning material for clinical skills training. Issue 1 (December 2016) - Haraldseid, Cecilie; Friberg, Febe; Aase, Karina
Abstract Background Policy initiatives and an increasing amount of the literature within higher education both call for students to become more involved in creating their own learning. However, there is a lack of studies in undergraduate nursing education that actively involve students in developing such learning material with descriptions of the students' roles in these interactive processes. Method Explorative qualitative study, using data from focus group interviews, field notes and student notes. The data has been subjected to qualitative content analysis. Results Active student involvement through an iterative process identified five different learning needs that are especially important to the students: clarification of learning expectations, help to recognize the bigger picture, stimulation of interaction, creation of structure, and receiving context- specific content. Conclusion The iterative process involvement of students during the development of new technological learning material will enhance the identification of important learning needs for students. The use of student and teacher knowledge through an adapted co-design process is the most optimal level of that involvement.